Bone mineral density prediction using MRI - Lee, Tat Kian. (2013)
The main aim of this project was to find out the relationship between mechanical properties of bones with imaging parameters such as magnetic resonance imaging (MRI), micro computed tomography (μCT) and bone mineral density (BMD). This is to determine the possibility of MRI to predict BMD and mechanical properties of bone, and as an alternative to current invasive techniques for predicting osteoporosis.